Research progress in preparation of polymer-derived SiC fibers containing hetero elements - WU Shuang; GOU Yanzi; WANG Yongshou; SONG Quzhi; XU Nana; HAN Cheng; WANG Yingde (Cailiao gongcheng, 2024)
Continuous SiC fibers reinforced SiC ceramic matrix composites have wide applications in the aerospace and nuclear fields owing to their excellent high-temperature resistance, good oxidation resistance and mechanical properties. The precursor-derived method has been the most important method for preparing continuous SiC fibers. The introduction of specific hetero elements could effectively improve properties of SiC fibers. Based on the research work on precursor-derived SiC fibers of high performance carried out by our group in the past forty years, this review firstly summarizes the addition methods of hetero elements, mainly including physical blending or chemical modification methods; The role and mechanism of hetero elements have been elucidated from several aspects: increasing the ceramic yield of the precursor, facilitating densification during sintering of the precursor-derived SiC fibers, improving high-temperature resistance of the final SiC fibers, and generating functions of SiC fibers; The composition, microstructure, properties, and developmental status of SiC fibers containing hetero elements, such as Ti, Al, Zr, Fe, B, as well as refractory metals (Hf, Ta, Nb), have been introduced. Furthermore, future research in the development of precursor systems, quantitative study of the relationship between the types and contents of hetero elements and properties of derived fibers, as well as engineering applications of the precursor-derived SiC fibers, has been prospected.